INSTITUTIONAL PROVISION OF ENERGY SECURITY IN THE CONTEXT OF DIGITALIZATION OF THE SOCIO-ECONOMIC SYSTEM: ENSURING THE SECURITY OF THE DIGITAL ECONOMY - Jallal, Abdul; Burkaltseva, Diana; Ostrik, Vladimir; Plaksa, Julia; Betskov, Aleksandr; Kilyaskhanov, Hizri (Revista Inclusiones, 2020)
The purpose of the article is to study the institutional provision of energy security in the context of the transformation of the socio-economic system on the example of the Russian Federation. The article uses general scientific methods of systemic, structural, complex, logical, statistical and economic analysis, an institutional approach is used.